Learning about a New Technology: Pineapple in Ghana - Conley, Timothy G; Udry, Christopher R (American Economic Review, 2010)
This paper investigates the role of social learning in the diffusion of a new agricultural technology in Ghana. We use unique data on farmers' communication patterns to define each individual's information neighborhood. Conditional on many potentially confounding variables, we find evidence that farmers adjust their inputs to align with those of their information neighbors who were surprisingly successful in previous periods. The relationship of these input adjustments to experience further indicates the presence of social learning. In addition, applying the same method to input choices for another crop, of known technology, correctly indicates an absence of social learning effects. (JEL D83, O13, O33, Q16)